Stuttering severity relates to frontotemporal low-beta synchronization during pre-speech preparation. (June 2022) - Korzeczek, Alexandra; Neef, Nicole E.; Steinmann, Iris; Paulus, Walter; Sommer, Martin
Highlights: The formation of the speech production network is linked to decreased posterior alpha and beta power. Fluent speech production relates to right frontotemporal beta power increase, which is pronounced in severe stuttering. Right frontotemporal beta power increase could reflect a necessary executive control for successfully implementing the task-set. Abstract: Objective: The neurophysiological dynamics of the occurrence of a stuttering event are largely unknown. This sensor-level EEG study investigated whether already the intention to speak alters the formation of the speech production network in stuttering. Methods: We studied alpha (8–13 Hz), low beta (15–25 Hz) and high beta (25–30 Hz) power modulation in 19 adults with developmental stuttering (AWS) and 19 fluently speaking control participants during speech intention. Results: Both groups show that the anticipation of overt reading coincides with broadband low-frequency suppression in posterior sensors, a common sign of network formation for speech production. Prior to fluent speech, frontotemporal alpha and low-beta power were weaker in AWS with mild stuttering but stronger in AWS with severe stuttering. These correlations were not significant prior stuttered speech. Further, post hoc comparisons confirmed the difference between AWS with mild and severe stuttering in low beta power. Conclusions: AWS with more severe stuttering seem to show stronger maintenance of the current cognitive or sensorimotor state, as stuttering severity was associated with increased beta power. Increased beta power levels may influence subsequent speech preparation and execution processes. Significance: Upcoming breakdowns of the speech production network as evident in actual stuttering are related to beta power during the intention to speak.